Analisis Pengaruh Pembangunan Infrastruktur Jalan, Listrik dan PMA terhadap Pertumbuhan PDRB Provinsi Bali tahun 1993-2014 - Sumadiasa, I Ketut; Tisnawati, Ni Made; Wirathi, I G.A.P. (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2016)
The infrastructure development is one of the important and vital aspect to accelerate the process of national and regional development. Infrastructure also plays an important role as a driver of economic growth. The purpose of this study was to analyze the direct and indirect effects of road infrastructure, electricity and FDI to GDP growth in the province of Bali. This study uses secondary data. Processing data using analytical techniques track / path analysis. Results showed construction of roads has a positive and significant correlation to the development of electricity infrastructure, construction of roads has a positive and significant impact on FDI, electricity has a positive effect but not significant to PMA. The road construction is positive but not significant effect on the growth of the GDP, while electricity has a positive and significant impact on GDP growth. FDI has a positive and significant impact on GDP growth and FDI is not a mediating variable in the effect of road infrastructure and electricity to the GDP growth.
Keywords: road; electricity; FDI; GDP growth.